DEVELOPMENT AND EVALUATION OF BETULINIC ACID CO-DELIVERED FEMARA LOADED DAMMAR GUM NANOPARTICLES TO FIGHT CANCER CELL LINE (International Journal of Food and Nutritional Sciences, 2022)
Chemotherapeutics approaches used to cure cancer are frequently faced a problem of drug resistances. Secondary metabolites of plants having anticancer potency can be effectively raised by formulating them at nanoscale. Betulinic acid (BA) is a pentacyclic triterpenoid molecule that has a potency to kill cancer cells by interfering in cellular proliferation. Femara (FEM) is an adjuvant molecule used to specially treat breast cancer. It is chemically known as Letrozole. To improve the bioavailability and to generate synergetic effect, BA and FEM loaded dammar gum nanoparticles (BFDNPs) were synthesized by oil in oil (O/O) emulsion solvent evaporation techniques. The zeta potential value of BFDNPs was come out to be -45.9 mV representing relative stability of nanoparticles. The percentage encapsulation efficiency value was found to be 72.5% for BA and 76.6% for FEM. The BFDNPs possess particle size in the range of 45 – 55nm as revealed by TEM. The BFDNPs exhibited sustained release and their anti-oxidant and anti-cancer potency was much more pronounced than free BA and FEM particles alone. The in vitro studies demonstrated that BA and FEM encapsulated in dammar gum inhibited growth of MCF-7 cell lines more effectively than BA and FEM alone which proved their robust anticancer potential.